Inflammatory imbalance in tracheal aspirate of very preterm newborns is associated with airway obstruction and lung function deficiencies at school age: a cohort study - Cecilia Hagman; Ellen Tufvesson; Ingrid Hansen Pupp; Lars Björklund (BMJ Publishing Group, 2024)
Objective A low expression of club cell secretory protein (CC16) and high levels of proinflammatory cytokines at preterm birth are associated with airway inflammation and more severe neonatal lung disease. The present study aimed to investigate if low levels of CC16, proinflammatory cytokines and vascular endothelial growth factors (VEGF) in tracheal aspirate early after birth were associated with lung function impairment at school age.Patients and methods Participants were 20 children, born very preterm (median gestational age 25+3 weeks+days, IQR: 24+1-27+0 weeks+days), who had tracheal aspirates collected during mechanical ventilation in their first day of life. CC16, cytokines, VEGF and matrix metalloproteinase-9 were measured in the tracheal aspirate and later correlated to results from advanced lung function measurements at 12 years of age.Results Low levels of CC16 and high levels of the proinflammatory cytokines IL-1β and TNF-α in tracheal aspirate were associated with airway obstruction at school age but not with other lung function parameters. The correlation with airway obstruction was even stronger when the ratio between the respective proinflammatory cytokine and CC16 was used. In addition, low levels of VEGF and CC16 were associated with impaired diffusion capacity of the lung.Conclusions An imbalance in inflammatory mediators and growth factors in the lungs at birth may have consequences for airway function and vasculature at school age in preterm born children.